INDONESIAN PRIVATE UNIVERSITY STUDENTS' PERCEPTION OF ENGLISH PODCAST INTEGRATION IN EFL SPEAKING LEARNING CLASSROOM - Saifullah, Saifullah (English Education Journal, 2024)
The integration of digital resources in language learning has become increasingly significant, especially with the advent of various multimedia tools. Among these, English podcasts have emerged as a valuable resource for enhancing students’ communication skills, particularly in Indonesian EFL classroom. Despite the widespread use of digital tools in language learning, there is still limited research on the integration of English podcasts to improve English department students’ speaking skills at an Indonesian university context. This study aims to investigate the students’ perceptions as well as their awareness of the drawbacks of podcasts on their English speaking skills development. Using the semi-structured interview, data were collected from 36 students who were enrolled in English education undergraduate programs at the private university in southeast Sulawesi province, Indonesia. Findings of this research were classified into three categories that are integration of podcast in EFL speaking classroom, benefits of podcasts, and drawbacks of podcasts. Students expressed positive attitudes towards the integration of podcasts into their English speaking learning routine, highlighting the role of presentation, accessibility, content quality, flexibility, and engagement. However, challenges such as the need for guidance, support, and boredom in using these digital tools were also identified. These findings provide significant insights for educational policies and language teaching practices, emphasizing the potential integration of podcasts as a supplementary tool to improve learners English speaking skills in EFL contexts.